Gender And Media Preference In Cosmetic And Hygienic Products: A Study In Iran - Bagheli, Tayebeh (2009)
This study is intended to investigate the relationship between gender and media preference along with the opinion of customers regarding cosmetic and hygienic products. how gender may influence customers' choice of different media. This includes media habits and media consumptions of customers that provide marketers with insight into customer behavior with respect to communication channels.